The functioning of alpine grassland ecosystems: Climate outweighs plant species richness - Cheng, Zhen; Zhao, Jingxue; Ding, Luming; Shi, Zhi‐Hua; Kardol, Paul; Wu, Gao‐Lin (The Journal of ecology, 2023)
The biodiversity–ecosystem functioning relationship has received significant attention in recent decades. It has been widely demonstrated that plant diversity plays a crucial role in enhancing the functioning of terrestrial ecosystems. However, few studies have tested the influence of plant species richness in mediating the impacts of climate on ecosystem functions at large spatial scales. To address this gap, we utilized data from field surveys across broad climatic gradients at the Qinghai–Tibetan Plateau, China. Our goal was to examine the importance of plant species richness for the functioning of alpine grassland ecosystems, specifically productivity and soil carbon sequestration. Our results showed strong positive correlations between ecosystem functioning and growing season precipitation as well as species richness. In contrast, there was a negative correlation with growing season temperature. Notably, the positive effect of growing season precipitation on ecosystem functioning outweighed the negative effect of growing season temperature. The indirect effects of growing season precipitation and temperature on ecosystem functioning through changes in species richness were weak. Furthermore, the inclusion of climate factors in the model weakened the relationships between species richness and ecosystem functioning. Synthesis . Our findings demonstrate that climate factors are more important than species richness for the provisioning of ecosystem functions at large spatial scales. In summary, our study underscores the importance of considering climate factors alongside species richness when assessing ecosystem functioning across extensive geographical areas. 近几十年来，生物多样性与生态系统功能的关系备受关注。众多研究广泛报导了植物多样性在增强陆地生态系统功能方面发挥着至关重要的作用。然而，很少有研究在大空间尺度上测试植物物种丰富度在调节气候对生态系统功能影响方面的作用。 为了填补这一空白，我们利用青藏高原东缘跨气候梯度的野外调查数据研究了植物物种丰富度对高寒草地主要生态系统功能的作用，尤其是生产力和土壤碳固存。 研究结果表明草地生态系统功能与生长季降水和物种丰富度呈显著正相关，而与生长季温度呈负相关。值得注意的是，生长季降水对高寒草地生态系统功能的积极影响超过生长季温度的消极影响。生长季降水和温度通过调节物种丰富度变化对高寒草地生态系统功能的间接影响较弱。此外，将气候因子纳入模型削弱了物种丰富度与生态系统功能之间的关系。 综述:研究结果表明在大空间尺度上，气候因子(降水和温度)比物种丰富度对草地生态系统功能维持的贡献更大。总之，我们的研究强调在评估大区域的生态系统功能时，需同时考虑物种丰富度和气候因子的重要性。